Perancangan Ulang Terminal Guntur Melati Garut Dengan Pendekatan Lokalitas - Kusuma Dewi, Tiara; Salayanti, Santi; Murdowo, Djoko (eProceedings of Art & Design, 2024)
Terminal Guntur Melati Garut is a Type A Bus Terminal located in Garut Regency that serves inter-provincial transportation (AKAP) and intra-provincial transportation within the province (AKDP). As a Type A terminal, the facilities at Terminal Guntur Melati are divided into main facilities such as waiting rooms and administrative buildings, as well as supporting facilities like toilets, mosques, food courts, and health rooms. According to data from the Directorate General of Land Transportation, Balai Pengelola Transportasi Darat Class II West Java, the average monthly passenger volume reaches 216,327 people with 18,635 buses per month. During the 2023 Nataru holidays, there was a 65% increase in arrivals. To attract public interest in mass transportation, Terminal Guntur Melati Garut has implemented various innovations such as live music, martial arts activities for children, local Garut culinary bazaars, and education related to transportation and road safety. The Ministry of Transportation supports the terminal's development with a "Mix Use" concept, making it a hub for social, economic, artistic, and cultural activities. However, the current interior of Terminal Guntur Melati Garut does not strongly represent local Garut culture. Therefore, a redesign of the terminal's interior with a focus on local Garut elements is expected to meet modern terminal standards and serve as a means to promote Garut's culture. Elements such as those from Kampung Adat Pulo, Batik Garutan ornaments, and unique Garut arts will be applied to the terminal's interior elements, providing a new experience for visitors to feel the local essence of Garut. Keywords: bus station, tipe a, locality